Impact of Compensation, Work Motivation, and Job Insecurity onTurnover Intention Driver Star Travel - Arzelya Zelda Sevira; Mei Retno Adiwati (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose: This study aims to analyze the influence of compensation, work motivation, and job insecurity on turnover intention of Star Travel drivers. Methodology: The sampling method in this study used a saturated sample containing 51 employees, and the analysis was carried out using the Partial Least Square Technique. The data were processed from a questionnaire with a Likert-based weighting scale. Results: it was found that compensation and work motivation had a negative and significant influence on turnover intention of Star Travel drivers. Meanwhile, job insecurity had a positive and significant influence on turnover intention of Star Travel drivers. Findings: This study found that job insecurity has a bigger influence on turnover intention compared to compensation and work motivation. Novelty & Originality: This study focuses on the problems that cause employee turnover intention in this company, which have not been previously studied. Conclusion: This study concludes that to reduce turnover intention, it is necessary to provide an understanding value of the benefits provided, evaluate employee motivation, and provide training to minimize errors made by employees. Type of Paper: Empirical research paper.